EVALUASI IN VITRO TERHADAP KEMAMPUAN ISOLAT Lactobacillus plantarum 1 DALAM MENGASIMILASI KOLESTEROL DAN MENDEKONJUGASI GARAM EMPEDU - Andre ' Pranata; Yusmarini ' '; Netti ' Herawati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Several studies have shown that lactid acid bacteria can reduce cholesterol. The aim of the study was to evaluate the ability of Lactobacillus plantarum 1 that isolated from spontaneous fermented soymilk in reducing cholesterol by assimilation and by bile salt conjugation. Experimental method used to test the ability of Lactobacillus plantarum 1 R.1.3.2, Lactobacillus plantarum 1 R.11.1.2, Lactobacillus acidophilus FNCC 0051 and Streptococcus thermophilus FNCC 0040 to assimilate cholesterol and to deconjugate bile salt. Cholesterol assimilation activity was determined by measuring the difference between remaining cholesterol in control medium and medium that inoculated by LAB. Bile salt deconjugation ability of LAB was determined by measuring free cholic acid released. The result showed that Lactobacillus plantarum R.11.1.2 and R.1.3.2 can assimilate cholesterol 0,56 µg/ml dan 0,48 µg/ml and can deconjugate sodium taurocholic 0,55 µmol/ml and 0,58 µmol/ml. Lactobacillus acidophilus FNCC 0051 and Streptococcus thermophilus FNCC 0040 can assimilate cholesterol 0,38 µg/ml dan 0,49 µg/ml and can deconjugate sodium taurocholic 0,58 µmol/ml and 0,55 µmol/ml. Keywords: Spontaneous fermented soymilk, lactic acid bacteria, cholesterol assimilation, Bile salt deconjugation.